Linguistic Competencies Required for Teachers of the Arabic Language for the Preparatory Stage (Journal Of Educational and Psychological Researches, 2023)
The current research aims to determine the necessary linguistic competencies for Arabic language teachers of the preparatory stage (fourth grade preparatory), which were five main competencies: Arabic grammar competencies, literary competencies, cultural competencies, rhetorical competencies, and expression competencies. To achieve the objective of the research, the researcher developed a questionnaire as the main tool for collecting data based on literature, it consists of (28) items including the five main competencies. The questionnaire was administered to (60) male and female teachers at Al-Karkh's first Education Directorate in the city of Baghdad. The findings of the research indicated that Arabic language proficiency got the highest percentage compared to the other competencies. Thus, the researcher presented a number of recommendations, including a list of linguistic competencies in the courses of methods of teaching the Arabic language for teachers in the preparatory stage indicating the importance of their acquisition of it.